Komposisi kimia, mineral, dan vitamin crackers prebiotik dengan penambahan garam rumput laut: Chemical composition, mineral, and vitamin of prebiotic crackers with addition of seaweed salt - Asadatun Abdullah; Nurjanah Nurjanah; Anggrei Viona Seulalae; Anita Nurul Firdaos (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Prebiotic food has become a food consumption trend because of its health benefits, especially for the prevention of stunting in toddlers and children. Mocaf flour combined with pea powder and seaweed salt can be processed into high-protein and high-mineral prebiotic crackers. This study aimed to determine the chemical composition, minerals, and vitamins of prebiotic crackers supplemented with Sargassum polycystum salt. This study consisted of making crackers without seaweed salt (F0) and with 2% seaweed salt (F1), followed by testing the chemical composition, minerals, and vitamins. The data were processed using Microsoft Office Excel 16 and descriptively analyzed. The results showed that prebiotic crackers with the addition of 2% S. polycystum salt increased the ash and lipid content but decreased the moisture, carbohydrate, and dietary fiber contents. Prebiotic crackers with and without the addition of S. polycystum salt had appropriate protein content appropriate SNI 2973:2018 about biscuit, namely 8.72% (F0) and 8.63% (F1). Prebiotic crackers with addition of S. polycystum salt has mineral content Na (389.72 mg/100 g), K (1,271.60 mg/100 g), Ca (224.61 mg/100 g), Mg (73.83 mg /100 g), Fe (4.22 mg/100 g), and vitamin B6 (7.02 mg/100 g). The addition of salt can increase the mineral and vitamin contents of prebiotic crackers.